The power of your subconscious mind - Murphy, Joseph (Simon & Schuster UK Ltd., 2018)
This authorised edition of Dr. Murphy's keystone work is the first premium mass market edition to feature additional commentary drawn from his unpublished writings. As practical as it is inspiring, Dr. Murphy's work demonstrates with real-life examples the way to unleash extraordinary mental powers to build self-confidence, create harmonious relationships, gain professional success, amass wealth, conquer fears and phobias, banish bad habits, and even to effect physical healing and promote overall wellbeing and happiness.